1991
DOI: 10.1159/000461244
|View full text |Cite
|
Sign up to set email alerts
|

Posttransfusion Fulminant Hepatitis B Associated with Precore-Defective HBV Mutants

Abstract: Fulminant hepatitis B developed in 8 recipients of blood units without detectable hepatitis B surface antigen on routine screening. All 124 hepatitis B virus (HBV) DNA clones propagated from their sera possessed defects in the precore region. A point mutation from guanine to adenine at nucleotide 83, converting codon 28 for tryptophan (TGG) to a stop codon (TAG), was the commonest, and it was found in all 113 clones from 7 cases. The remaining case displayed 1 clone with this point mutation and 10 clones with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Elsewhere, donations are tested for antibodies to hepatitis B core antigen,8 which can detect infectious donors undetectable by tests for hepatitis B surface antigen 9. In the United States, testing for antibody to hepatitis B core antigen may prevent 33% to 50% of cases of hepatitis B potentially transmissible from donors who test negative for hepatitis B surface antigen 10.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, donations are tested for antibodies to hepatitis B core antigen,8 which can detect infectious donors undetectable by tests for hepatitis B surface antigen 9. In the United States, testing for antibody to hepatitis B core antigen may prevent 33% to 50% of cases of hepatitis B potentially transmissible from donors who test negative for hepatitis B surface antigen 10.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the presence of core promotor and precore mutations in the transmitted virus may have effects on the HBV DNA and HBsAg expression in the recipient and be associated with a higher risk of an occult (HBsAg‐negative) course or fulminant hepatitis 19‐21 in the acute stage. Infection with these mutations, however, is not predictive for an occult course in the acute phase, because we saw three donors infected with mutant virus (Donors 7, 11, and 13) that developed detectable HBsAg for an estimated period of 28 to 40 days.…”
Section: Discussionmentioning
confidence: 99%
“…16 17 There have been a few reports that have described a relationship between precore mutations and fulminant hepatitis (FH). [18][19][20][21][22][23] Similarly, Sato et al reported the presence of an A to T mutation at nt 1762 and a G to A mutation at nt 1764 in the core promoter region (T1762 and A1764) in Japanese patients with FH who did not manifest precore stop codon mutations. 24 However, a study of patients from the USA and Europe failed to reveal such an association.…”
mentioning
confidence: 99%